Strategic business models in the car-based shared mobility: recommendations on how to improve the free-floating car sharing business model - Grilo, Francisco Carvalho Lourenço (2023)
The mobility industry along with the automotive industry is currently evolving due to several global conditions which include traffic jams, pollution, and climate change. New technologies, sustainability awareness, and shared mobility are empowering the development of new strategic business models. This paper analyzes the business model evolution of car-based shared mobility in Europe while understanding the changes in customer behaviors regarding car usage. A detailed explanation of the car-sharing free-floating business model is pointed out and evaluated along with the development of recommendations focusing on improving the benefits and reducing the drawbacks that emerged within the research.